Is RAS the Link Between COVID-19 and Increased Stress in Head and Neck Cancer Patients? - Iftikhar, Anem; Islam, Mohammad; Shepherd, Simon; Jones, Sarah; Ellis, Ian (Frontiers in Cell and Developmental Biology, 2021)
The COVID-19 pandemic emerged as a largely unexplained outbreak of pneumonia cases, in Wuhan City, China and rapidly spread across the world. By 11th March 2020, WHO declared it as a global pandemic. The resulting restrictions, to contain its spread, demanded a momentous change in the lifestyle of the general population as well as cancer patients. This augmented negative effects on the mental health of patients with head and neck cancer (HNC), who already battle with the stress of cancer diagnosis and treatment. The causative agent of COVID-19, SARS-CoV2, gains entry through the Angiotensin converting enzyme 2 (ACE2) receptor, which is a component of the Renin Angiotensin System (RAS). RAS has been shown to influence cancer and stress such that it can have progressive and suppressive effects on both, cancer and stress. This review provides an overview of SARS-CoV2, looks at how the RAS provides a mechanistic link between stress, cancer and COVID-19 and the probable activation of the RAS axis that increase stress (anxiogenic) and tumor progression (tumorigenic), when ACE2 is hijacked by SARS-CoV2. The mental health crises brought about by this pandemic have been highlighted in many studies. The emerging links between cancer and stress make it more important than ever before to assess the stress burden of cancer patients and expand the strategies for its management.